Location of entrepreneurial zones in Latin America: a spatial analysis - Frende-Vega, María (2025)
This study analyzes spatial patterns in the entrepreneurial intention of university students in Latin America. Studies on the entrepreneurial phenomenon have paid little attention to possible spatial associations, which might explain the dissimilar resultsreported by prior work. The analysis uses a sample of 70,337 university students drawn from the GUESSS survey. The results of the exploratory spatial model reveal significant spatial patterns in Costa Rica and Panama with a high entrepreneurial intention (hot spots). This study can serve as a basis for developing public policies to promote entrepreneurship and, when appropriate, propose articulated and coordinated strategic initiatives between countries located in the identified clusters (hot/cold spots).